ANALISIS PENERAPAN PPN DAN PPh PASAL 22 ATAS PENGADAAN BARANG PADA BENDAHARAWAN NEGARA DEPUTI BIDANG INDUSTRI DAN INVESTASI, KEMENPAREKRAF - Simarmata, Jahormin; Natrion; Dian Mahardika (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
The purpose of this research, namely to determine the application of Value Added Tax (VAT) and Income Tax (PPh) Article 22 to the procurement of goods at the state treasurer of the Deputy for Industry and Investment, Kemenparekraf. The tax data used comes from year on 2022. Descriptive qualitative research was used in this research, with samples taken from one year of the research. According to the findings of the research, reporting is a problem point in the application of VAT and Income Tax Article 22 on the procurement of goods at the state treasurer of the Deputy for Industry and Investment, Kemenparekraf due to delays in reporting the Unified Periodic Tax Return on VAT and Income Tax Article 22. It is expected that state treasurers follow tax technical guidance and a qualified system is made which aims to minimize delays in reporting the Unified Periodic Tax Return on VAT and Income Tax Article 22